From farm to HORECA: advancing sustainable value chains for tourism-driven agribusiness in Indonesia - Utama, I Made Supartha; Widia, I Wayan; Arthawan, I Gusti Ketut Arya; Badgery Parker, Jeremy; Arya, Nyoman Ngurah; Sayaka, Bambang; Widyastuti, Sri; Dahlanuddin; Djarkasi, Gregoria S. Suhartati; Sumual, Maria Fransisca; Sumendap, Andreas Leonardo (Frontiers in Sustainable Food Systems, 2025)
Agri-food value chains in Indonesia's tourism economies offer strategic opportunities for inclusive rural–urban linkages but remain hindered by persistent constraints in finance, logistics, and digital innovation. This study investigates the conditions that enable or constrain sustainable, inclusive, and efficient farm-to-HORECA (Hotels, Restaurants, and Catering) value chains across three provinces in Indonesia—Bali, Lombok-West Nusa Tenggara (WNT), and North Sulawesi—using a mixed-methods design comprising structured surveys (n = 370), in-depth interviews (n = 60), and participatory workshops. Results reveal critical bottlenecks: 91.1% of farmers rely on personal savings, only 16.9% of in-chain actors adopted new technologies in the past 5 years, and formal collaboration remains extremely limited. HORECA actors demonstrate operational resilience and support inclusive principles, yet upstream engagement is weak and perceptions of regulatory benefit are low across sectors (farmers 13.3%, in-chain 8.5%). Nonetheless, significant correlations were found between inclusivity, organizational innovation (r ≥ 0.6), and perceptions of regional development. These findings underscore the need for integrated interventions—combining localized policy support, financial inclusion tools, digital platforms, and cooperative governance models—to strengthen value chain connectivity and performance. By identifying leverage points across farm, midstream, and market segments, this study contributes to the literature on inclusive agri-food systems and offers actionable insights for achieving SDGs 2 (Zero Hunger), 12 (Responsible Consumption and Production), and 17 (Partnerships for the Goals) in middle-income, tourism-dependent economies.